THE INFLUENCE OF EMPLOYEE SELECTION PROCESS ON EMPLOYEE PERFORMANCE AT THE CAMMING SUGAR FACTORY - Dirgahayu Lantara; Abd Mail; A. Sriani Bulqis; Anis Saleh; Nur Ihwan Saputra; Rahmaniah Malik; Nurul Chairany; Taufik Nur (Journal of Industrial Engineering Management, 2022)
Human resources are one of the resources that exist in the organization which consists of people and their activities this is the most resources compared to other resources. At the Camming Sugar Factory, human resources are the main means to achieve the desired goals of the company, especially in the production section in order to achieve maximum production results with the aim of maintaining the survival of the company and employees being able to perform optimally in the form of work productivity. To achieve this goal, qualified human resources are needed, one way is through a good and correct selection process. The performance of employees at the camming sugar factory is said to be less than good. This can be seen from the conditions that have occurred in the Camming sugar factory, namely the threat of bankruptcy with an average loss of more than Rp. 100 billion per year due to production results which are only 30 percent of the maximum potential since 2001. Based on the parameters that cause losses at the Camming Sugar Factory which is thought to be caused by weak management which is considered to be the main trigger, it is necessary to research and review what factors influenced the decline of the factory..The method used in this research is linear regression method, in which the method can determine the hypothesis and the relationship between the independent variable and the bound variable. The research results obtained from the coeficients table obtained a significance value of 0.000 0.05, so it can be concluded that the Selection variable (X) affects the Performance Variable (Y). From the statistical calculation of the t test, t count is 6,731 from t table then H1 is accepted and Ho is rejected. This means that there is a significant and positive effect of the employee selection process on the performance of employees at the Camming Sugar Factory. Thus the hypothesis is proven